Common Structural Patterns in the Maxicircle Divergent Region of Trypanosomatidae - Gerasimov, Evgeny S; Zamyatnina, Ksenia A; Matveeva, Nadezda S; Rudenskaya, Yulia A; Kraeva, Natalya; Kolesnikov, Alexander A; Yurchenko, Vyacheslav (Pathogens (Basel, Switzerland), 2020)
Maxicircles of all kinetoplastid flagellates are functional analogs of mitochondrial genome of other eukaryotes. They consist of two distinct parts, called the coding region and the divergent region (DR). The DR is composed of highly repetitive sequences and, as such, remains the least explored segment of a trypanosomatid genome. It is extremely difficult to sequence and assemble, that is why very few full length maxicircle sequences were available until now. Using PacBio data, we assembled 17 complete maxicircles from different species of trypanosomatids. Here we present their large-scale comparative analysis and describe common patterns of DR organization in trypanosomatids.
Keywords: kinetoplast; repeats; mitochondrion; maxicircle; genomic rearrangements; divergent region; trypanosomatids